Analysis of antioxidant properties and volatile compounds of honeys from different botanical and geographical origins - Kasful Asra Sakika,; Mohd Zuwairi Saiman,; Nor Hisam Zamakshshari,; Idris Adewale Ahmed,; Muhammad Nazil Afiq Nasharuddin,; Najihah Mohd Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Honey has been consumed since ancient time due to its nutritional and therapeutic values. Studies showed that honey possesses antioxidant properties which can inhibit oxidation and cell damage in the body. However, the chemical contents and antioxidant properties of honeys are varied, depending on botanical and geographical origins of honey. In this study, we analysed the total phenolic content (TPC), total flavonoid content (TFC), antioxidant properties (DPPH, ABTS, FRAP and TAOC) and volatile profiles of several commercial honeys originated from Malaysia, Turkey, and Yemen. The results showed that sample H4 (Pine honey) from Turkey was the highest in TPC (0.84 μg GAE/mg honey), ABTS (63.15% inhibition) and FRAP (0.45 μg FeSO4 equivalent/mg honey) values, while H2 (Acacia honey) from Malaysia showed the highest values in TFC (0.11 μg quercetin equivalent/mg honey) and DPPH (45.13 mg/mL IC50). Meanwhile, H5 (Marai honey) from Yemen recorded the highest TAOC value (24.14 μg ascorbic acid equivalent/mg honey). Twenty-four volatile compounds were identified using gas chromatography-mass spectrometry (GC-MS), among others are 4H-pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl, linoleic acid ethyl ester, 2,5-dimethyl-4-hydroxy-3(2H)-furanone, and 2,4-dihydroxy-2,5-dimethyl-3(2H)-furan-3-one which contribute to chemical characteristics of certain honeys. In regards to the TPC, TFC, and antioxidant assays, the honey samples were ranked based on the chemical properties level as follows: H4 (Pine honey) > H2 (Acacia honey) > H7 (Kelulut 2) > H3 (Kelulut 1) > H6 (Sumar honey) > H1 (Tualang honey) > H5 (Marai honey). This finding increases the knowledge of the chemical compositions, volatile compounds, and antioxidant activities of several commercial honeys derived from different botanical and geographical origins.